Stressful Life Events and Risk of Depression 25 Years Later: Race and Gender Differences - Assari, Shervin; Lankarani, Maryam Moghani (Frontiers in Public Health, 2016)
BACKGROUND: Although stressful life events (SLE) predict subsequent risk of developing a major depressive episode (MDE), limited information exists on whether or not race and gender alters the predictive role of SLE on risk of MDE over a long-term period. The current study explored race and gender differences in the long-term predictive role of SLE at baseline (1986) on subsequent risk of MDE 25 years later (2011) in a nationally representative cohort in the United States. METHODS: Using a life course epidemiological approach, this longitudinal study borrowed data from the Americans’ Changing Lives Study (ACL) 1986- 2011. Main predictor of interest was baseline SLE over the last three years measured at 1986. Main outcome was risk of MDE [Composite International Diagnostic Interview (CIDI)] 25 years later (2011). Covariates included demographics, socioeconomics, depressive symptoms (Center for Epidemiological Studies-Depression Scale [CES-D]), chronic medical conditions, and health behaviors measured at baseline (1986). Gender and race were the focal moderators. We employed logistic regressions in the pooled sample, and specific to race and gender, to test whether or not SLE × race and SLE × gender interactions are significant. RESULTS: In the pooled sample, baseline SLE (1986) predicted risk of MDE 25 years later (2011). We also found a gender by SLE interaction, suggesting a stronger predictive role of SLE for subsequent clinical depression for men compared to women. Race did not modify the predictive role of SLE on subsequent risk of MDE 25 year later. CONCLUSIONS: How SLE predicts MDE 25 years later differs for men and women, with a stronger predictive role for men, compared to women. More research is needed to better understand the complex links between gender, sex, stress, and depression.